British Parliament during Umpire of the Republic, 1649-1660 - Majid Abdel Zahr; Maytham Hashem Hussein; Ammar Kadeem Matar (Genius Journals, 2021)
Represented by the republican system, which came as a result of the development of English society and its need for constitutional data. Meet the capabilities of his class, social and economic development. England fought a serious internal political struggle between the king and Parliament, the most prominent of which was the execution of the king and the abolition of the monarchy in England after many centuries of that rule, and the imposition of a new system of government that England had not known before. In this study, the motives and reasons that led to the proclamation of the Republic were addressed, in addition, that, dealt with the work of the English Parliament during that period, and finally, talked about the most important problems and obstacles that faced Parliament, leading to the return of the monarchy.
Keywords: English society; Parliament; England; republican system